2015
DOI: 10.1108/intr-12-2013-0267
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of product placement in social media

Abstract: Purpose -The purpose of this paper is to focus specifically on the examination of factors influencing the effectiveness of product placement in social media. Design/methodology/approach -Two field experiments were used to test research models and questions. In each experiment, random sampling was used to assign volunteers into groups, controlled by different experimental settings. Questionnaires were distributed to the volunteers in order to collect their attitude toward advertisement, brand impression, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 37 publications
3
35
0
1
Order By: Relevance
“…Schivinski and Dabrowski (2015) discovered that both user-generated and organizational social media brand communications positively affected awareness (cognitive responses). Labrecque's (2014) Liu et al (2015) examined factors that influenced the effectiveness of social media product placement. The investigation established videos with subtle product placements, which resulted in the most favorable attitude and behavioral responses, and that the effect of social media product placements was comparable to other media.…”
Section: Social Media Marketing Communications' Influence On Young Comentioning
confidence: 99%
“…Schivinski and Dabrowski (2015) discovered that both user-generated and organizational social media brand communications positively affected awareness (cognitive responses). Labrecque's (2014) Liu et al (2015) examined factors that influenced the effectiveness of social media product placement. The investigation established videos with subtle product placements, which resulted in the most favorable attitude and behavioral responses, and that the effect of social media product placements was comparable to other media.…”
Section: Social Media Marketing Communications' Influence On Young Comentioning
confidence: 99%
“…In this light, we attempt to explore whether visual cues in web advertising (e.g., background color, images, and flash design) influence advertising outcomes as measured by advertising attitude, brand attitude, and online purchase intention. In an internet context, much research has shown that attractive and pleasurable site stimuli can enhance positive consumer responses Ching et al, 2013;Cho & Kim, 2012;Day, Shyi, & Wang, 2006;Flores et al, 2014;Kim, Kim, & Park, 2010;Liu, Chou, & Liao, 2015;Moore, Stammerjohan, & Coulter, 2005;Richard, 2005;Sokolik et al, 2014). Hence, the responses of online consumers may be influenced by visual attractiveness in web advertising as well.…”
Section: Web Advertising Visual Design (Wavd)mentioning
confidence: 99%
“…In addition, evaluation of the brand name was found to be dependent on its location in the advertisement (right vs. left) and the type of advertising stimulus (verbal stimulus vs. pictorial stimulus) (see Janiszewski, 1988Janiszewski, , 1993. Liu et al (2015) also theorized a positive relationship between the attractive placement of products and ATA. Additionally, several studies have examined the potential effect of site stimuli on visitors' responses Ching et al, 2013;Flores et al, 2014;Goodrich, 2014;Hwang, Yoon, & Park, 2011;Moore et al, 2005;Wu et al, 2008).…”
Section: The Effects Of Wavd On Advertising Attitude and Brand Attitudementioning
confidence: 99%
“…However, the effectiveness of IM platforms should also be considered from a more holistic perspective, since social media advertising has a significant effect on attitudes that cannot be determined solely by CTR (Williamson, 2012). Several studies have focused on the examination of online consumers' attitudes and usage (Kuisma et al, 2010;Punj, 2011;Mina, 2012;De Haan et al, 2013); and, more recently, social media (Malthouse et al, 2013;Maxwell, 2013;Weinberg et al, 2013;Hardwick et al, 2014;Hollebeek et al, 2014;Liu et al, 2015). A majority of these inquiries agree that the primary objective of online and/or social media advertising is to establish favorable attitudes towards organizations and their brands.…”
Section: Introductionmentioning
confidence: 99%